The Effectiveness Of Song Media ‘Kalam-Eineh’ To Arabic Vocabulary Teaching At Vocational High School Semarang: فعالية وسائط الأغاني "كلام عينيه" في تعليم المفردات بمدرسة-المركز-الإسلامى بيت الرحمن الثانوية الإسلامية المهنية سمارانج - Aminah, Laila Nur; Inayah, Inayah; Wahid, Abdul; Ramadlan, Muhammad Atif Audl (TSAQOFIYA : Jurnal Pendidikan Bahasa dan Sastra Arab, 2025)
من صعوبات تعليم اللغة العربية التي يواجه بها الطلاب للفصل العاشر بمدرسة  بيت الرحمن المركز الإسلامي الثانوية المهنية سمارانج SMK Islamic Centre Baiturrahman Semarang هي حفظ المفردات وفهمها من ناحية المعنى. ومن نتيجة الاختبار القبلى أنهم منخفض درجات حول المفردات حتى أنهم لا يفهمون اللغة العربية جيدا. فهذه النقطة خلفية الدراسة لهذا البحث. من الناحية الأخرى، أن  الأغانى "كلام عيناه" أحد الأغانى المنشورة في تيكتوك والوسائل الاتصالية خاصة في إندونيسيا وفي حالة الطلاب في تلك المدرسة.  هذه الفرصة مستخدمة لتطبيق الوسائط الأغانى "كلام عيناه" في تعليم المفردات  ومعرفة فعالية استخدامه في ترقية القدرة على المفردات للطلاب الصف العاشر من تلك المدرسة. أُخذت العينة من طلاب الصف العاشر قسم محاسبة المالية المؤسّسات Akuntansi Keuangan Lembaga (AKL) بمجموع 23 طالبًا.  تستخدم هذه الدراسة مدخلا كميًا بنوع الدراسة التجربية من نموذج مجموعة واحدة الاختبار القبلى والاختبار البعدى One group pretest-posttest experiment. طريقة جمع البيانات هي الملاحظة والتوثيق والاختبار (القبلى والبعدى). أما طريقة تحليل البيانات المستخدمة فهي تحليل الإحصاء الوصفى Descriptive Statistical Analysis من الانحراف المعيارى Deviation Standard ثم اختبار التجانس واختبار العينة المزدوجة Paired sample T-Test.  على أساس  اختبار t تم الحصول الدرجة  sig (2-tailed) هي 0.011 أنها أقل من 0.05. إذن H0 مرفوضة و Ha مقبولة. وهذا يعني أنه يوجد فرق كبير في المتوسط بين نتائج درجات الاختبار القبلى قبل التجربة والاختبار البعدى بعد التجربة أن استخدام وسائط الأغاني ”كلام عيناه“ لطلاب في الصف العاشر بمدْرَسَة المركز الإسلامي بيت الرحمن الثانوية المهنية سمارانج يكون فعالا لترقية كفاءة المفردات لهم Abstract One of the difficulties of learning Arabic experienced by tenth-grade students at SMK Islamic Centre Baiturrahman Semarang is memorizing and understanding vocabulary in terms of meaning. From the pre-test results, they have low scores in terms of vocabulary so they do not understand Arabic well. This is the background of this study. On the other hand, the song ‘Kalam Ainah’ is one of the songs that is widely circulated on Tiktok social media and communication media, especially in Indonesia, and in this case, students at the school.  This opportunity was used to apply the ‘Kalam Ainah’ song media in vocabulary teaching and determine the effectiveness of its use in improving the vocabulary skills of grade 10 students in the school. The sample was taken from the 10th-grade students of Institutional Financial Accounting (AKL) with a total of 23 students. This study used a quantitative approach with a one-group pretest-posttest experiment type of research. The data collection methods used were observation, documentation, and tests (pre-test and post-test). The data analysis methods used are Descriptive Statistical Analysis of Standard Deviation, Homogeneity Test, and Paired sample T-Test.  Based on the t-test, the sig (2-tailed) value is 0.011 which is smaller than 0.05. So H0 is rejected and Ha is accepted. This means that there is a significant average difference between the pre-test score before the experiment and the post-test score after the experiment that the use of ‘Kalam Eineh’ song media for grade 10 students at Islamic Centre Baitul Rahman Semarang Vocational High School is effective to improve their vocabulary competence.